CONSERVATION OF CULTURAL HERITAGE AND ITS RELATIONSHIP WITH TOURISM - Shomurodova Ozoda Uygun qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
Most people are tourists, almost everywhere. The guests in cultural institutions and sites have different levels of prior knowledge, are different in their expectations and motives differently predisposed - and that is exactly the challenge for the cultural bearer and for an intelligent one visitor management, acting in the interest of the guest and in terms of cultural assets. Culture does not take place on an island of the blessed. Cultural institutions are not outside of economic cycles, they are links in complex value-added chains, and that is true no contradiction to the public order. On the contrary: by thinking and acting economically, cultural institutions expand the scope of action within the scope of their mandate and make them more effective.